O TikTok e o Ensino de Danças Urbanas - Neves, Deyzylany Ferreira (2024)
Physical Education, by relying on critical theories of education, seeks to overcome the borderline perspective of apprehension and development of motor skills, aiming to provide students with access to socio-historical knowledge of body culture. From this perspective, we seek to develop innovative pedagogical practices from this field of knowledge that enable the formation of critical citizens who are aware of the multiplicity of knowledge related to the body, beyond biological and/or instrumental reductionism. In the current context, urban dances have gained increasing prominence among young people, being an artistic and cultural expression that promotes well-being and creativity. However, the teaching of these dances in Physical Education classes often remains traditional and limited, not fully exploiting the educational and engaging potential they offer. In this sense, there is a need to explore new pedagogical approaches, incorporating the use of contemporary tools to make the teaching of urban dance more effective and attractive. This work aims to analyze how TikTok, a video sharing platform, can become a pedagogical tool in teaching urban dances in Physical Education, aiming to provide students with a more meaningful and enriching experience. To carry out this research and through a study of art, we based ourselves primarily on the following authors, Barin, Ellensohn (2020); Silva, Morais and Costa (2022), which brings the limits and possibilities of working with urban dances at school, and Guarato (2020), with the clarification of the origin of urban dances and their historical transformations, as well as their foundations and its constituent elements. In addition to TikTok's academic production, to present and discuss the advantages and challenges of experiencing this application as an educational tool. Furthermore, the work was developed during the Stricto Sensu Professional Master's Degree of the Postgraduate Program in Teaching in Basic Education at the Center for Teaching and Research Applied to Education (CEPAE) at the Federal University of Goiás (UFG). The research is bibliographical and qualitative in nature, complemented by documentary analysis, which deepened the theoretical/practical dimensions of the teaching-learning process of urban dances in school education using the social network TikTok as a pedagogical tool. The literature presented highlights the relevance of using this social network as a pedagogical tool in teaching urban dances in Physical Education from different perspectives, highlighting both its advantages and student motivation (Alves and Diaz, 2004; Camargo and Vieira, 2017), as concerns about superficiality and cultural appropriation (Silva, 2020). As an extension of the research, he developed an educational product, entitled "Urban Dances on TikTok", with a class sequencer for teaching urban dances in the Physical Education discipline, using TikTok as a pedagogical tool.